2009
DOI: 10.1128/iai.01306-08
|View full text |Cite
|
Sign up to set email alerts
|

First Streptococcus pyogenes Signature-Tagged Mutagenesis Screen Identifies Novel Virulence Determinants

Abstract: The virulence of bacterial pathogens is a complex process that requires the dynamic expression of many genes for the pathogens to invade and circumvent host defenses, as well as to proliferate in vivo. In this study, we employed a large-scale screen, signature-tagged mutagenesis (STM), to identify Streptococcus pyogenes virulence genes important for pathogenesis within the host. Approximately 1,200 STM mutants were created and screened using the zebrafish infectious disease model. The transposon insertion site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
51
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 64 publications
(82 reference statements)
1
51
0
Order By: Relevance
“…For example, Neely and colleagues found that Streptococcus pyogenes (a human pathogen) and Streptococcus iniae (a natural patho- on May 10, 2018 by guest http://iai.asm.org/ gen of fish) infect adult zebrafish at similar efficiencies, and the comparable results support the conclusion that the Streptococcus-zebrafish model can be used to study human pathogenic bacteria (31). By employing large-scale, signature-tagged mutagenesis, 1,200 different mutant S. pyogenes strains were screened with the zebrafish infection model to identify virulence genes of the bacterial pathogen, which is important in S. pyogenes pathogenesis (18). The zebrafish model has also been used in studies of other bacteria, including studies of chronic tuberculosis caused by Mycobacterium marinum infection, realtime analysis of Salmonella enterica serovar Typhimurium infection, and analysis of Listeria monocytogenes-phagocyte interactions (22,25,37,41).…”
Section: Discussionmentioning
confidence: 62%
“…For example, Neely and colleagues found that Streptococcus pyogenes (a human pathogen) and Streptococcus iniae (a natural patho- on May 10, 2018 by guest http://iai.asm.org/ gen of fish) infect adult zebrafish at similar efficiencies, and the comparable results support the conclusion that the Streptococcus-zebrafish model can be used to study human pathogenic bacteria (31). By employing large-scale, signature-tagged mutagenesis, 1,200 different mutant S. pyogenes strains were screened with the zebrafish infection model to identify virulence genes of the bacterial pathogen, which is important in S. pyogenes pathogenesis (18). The zebrafish model has also been used in studies of other bacteria, including studies of chronic tuberculosis caused by Mycobacterium marinum infection, realtime analysis of Salmonella enterica serovar Typhimurium infection, and analysis of Listeria monocytogenes-phagocyte interactions (22,25,37,41).…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, a systematic sequencing of the silCR gene in emm14 strains is necessary to determine whether the described mutation is an exception or the rule among the emm14 strains (13,19). Nonetheless, a similar mutation was reported for an additional emm14 strain isolated in the United States (15).…”
Section: Discussionmentioning
confidence: 99%
“…This in turn activates the transcription of silCR (autoregulation) and silD and silE and represses that of silC (14). The silC gene product is linked to GAS virulence in the mouse model of human NF (13,15). SilCR is involved in the downregulation of the expression of the gene encoding the CXC chemokine protease ScpC, which impairs the recruitment and the activation of neutrophils to the soft tissue infection site (16,17).…”
mentioning
confidence: 99%
“…2,3,[5][6][7][8][9][10]15 In this review we will focus on STM screens associated with gastrointestinal (GI) infections ( Table 1). GI illness is a global public health concern and in the developed world it is usually self-limiting but has a considerable economic burden.…”
Section: Introductionmentioning
confidence: 99%
“…STM was initially developed to identify virulence genes in Salmonella enterica serovar typhimurium but has subsequently been used in many screens in other bacterial species as well as in the yeast Saccharomyces cerevisiae, the fungus Cryptococcus neoformans and the parasite Toxoplasma gondii. [1][2][3][4][5][6][7][8][9][10] For any bacterial pathogen there are several critical parameters that must be followed in order to ensure an efficient STM screen in vivo. First, the transposon chosen should insert randomly into the chromosome, a property which varies depending on the transposon.…”
Section: Introductionmentioning
confidence: 99%